2023
DOI: 10.1136/bmjhci-2022-100726
|View full text |Cite
|
Sign up to set email alerts
|

Electronic consent in clinical care: an international scoping review

Abstract: ObjectiveDigital technologies create opportunities for improvement of consenting processes in clinical care. Yet little is known about the prevalence, characteristics or outcomes of shifting from paper to electronic consenting, or e-consent, in clinical settings. Thus questions remain around e-consent’s impact on efficiency, data integrity, user experience, care access, equity and quality. Our objective was to scope all known findings on this critical topic.Materials and methodsThrough an international, system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Literature on patient and staff satisfaction with e-consent in clinical practice is nascent, but some studies have shown a preference for e-consent [22], and higher shared decision-making scores have been demonstrated [7,23]. E-consent has been widely used in medical research, and studies have shown similar findings, in which e-consent participants are satisfied and can have a better understanding of information, but there are issues with using technology and authentication [24].…”
Section: Discussionmentioning
confidence: 99%
“…Literature on patient and staff satisfaction with e-consent in clinical practice is nascent, but some studies have shown a preference for e-consent [22], and higher shared decision-making scores have been demonstrated [7,23]. E-consent has been widely used in medical research, and studies have shown similar findings, in which e-consent participants are satisfied and can have a better understanding of information, but there are issues with using technology and authentication [24].…”
Section: Discussionmentioning
confidence: 99%
“…Methods such as computerized consent and consent to share with specific prenatal resources can be incorporated into test requisition forms in collaboration with clinics and testing laboratories. [34][35][36][37][38][39] Given that the agreements can be challenging to arrange due to varied institutional processes, streamlining such processes can drastically reduce the logistical hurdles for data sharing. Finally, through resources such as GenomeConnect, 40 individuals can be directly engaged in collaboration with a sequencing laboratory.…”
Section: Data Identification Generation and Collectionmentioning
confidence: 99%
“…There are also the intangible benefits of patient and doctor satisfaction along with improved delivery of health care if extended to areas such as electronic consent. 45…”
Section: Implement a Paperless Systemmentioning
confidence: 99%